JUNIOR HIGH SCHOOL STUDENTS’ INTRINSIC MOTIVATION IN LEARNING ENGLISH USING MULTIMEDIA - Emil Yani; Nina Suzanne; Sirajul Munir; Silfia Rahmi (Universitas Bina Bangsa Getsempena, 2026)
The consistent use of multimedia by student teachers in English language instruction has been recognized to enhance students’ motivation and learning outcomes. This study aimed to examine students’ intrinsic motivation in learning English through multimedia. A quantitative approach with a survey design was employed. The sample consisted of 31 students from grades VII and VIII at a junior high school in Salimpaung, Tanah Datar, selected using a total sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed descriptively with SPSS version 30.0. The findings indicate that students’ intrinsic motivation in learning English using multimedia was generally at a moderate level. Across the five dimensions of intrinsic motivation, students demonstrated high levels of enjoyment of the learning process, desire to succeed, encouragement to learn, and interest in learning, while their hope of achieving learning goals remained at a moderate level. These findings suggest that multimedia can support students’ engagement and intrinsic motivation in English learning, although the level of motivation was not consistently high across all dimensions. The findings imply that English teachers should integrate multimedia with appropriate instructional strategies to better foster students’ intrinsic motivation and create more engaging learning experiences in EFL classrooms.